Kombinasi Perlakuan Suhu, Lama Perendaman dan Jenis Air Terhadap Perkecambahan Benih Trembesi (Samanea saman (Jacq.) Merr.): Combination of temperature treatment, saoking time and water on Trembesi Seed (Samanea saman (Jacq.) Merr.) Germination - Sudomo, Muhammad Fadhil Amiruddin; Dwiastuti, Rini; Madiyawati, Milad; Koroh, Desy Natalia; Tambun, Kesia Br Tarigan (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
This study aims to determine the effect of seed soaking temperature in room temperature water (240C) and (600C), determine the effect of soaking time at the level of 0 hours (control), 6 hours, 12 hours, 18 hours, determine the effect of the type of soaking water, namely Kahayan River water, Peat water, PDAM water, Aquades water, and determine the effect of all the best interactions on the germination of Trembesi tree seeds. The research method used a complete randomized design (CRD) Factorial A x B x C, each factor A = 2 levels namely A1 (240C) and A2 (600C), factor B = 4 levels namely B1 (0 hours) without control, B2 (6 hours), B3 (12 hours), B4 (18 hours), factor C = 4 levels namely C1 (khayan river water), C2 (peat water), C3 (PDAM water), C4 (distilled water) with 3 replicates. The results showed that water with a temperature of 600C for a soaking time of 6 hours and soaking in peat water produced the best germination of Trembesi tree seeds because the temperature can help the process of breaking down food reserves so that enzymes work well and soaking for 6 hours can absorb water so that the softening of the seed coat and the development of the seed coat and the soaking water used has a high content of organic matter and carbon substances that are acidic with a pH of 3.8 which can soften the seed coat so as to accelerate the germination process. The interaction factor of temperature, soaking time, and soaking water (AxBxC) at a temperature of (600C) for 6 hours using peat water produces the best germination of Trembesi tree seeds.